Improving QOS in flow controlled CR-ad hoc network with multi criteria routing assisted with cooperative caching and information redundancy. (14th June 2022) - Reddy, C.V. Subhaskar; Subramanyam, M.V.; Reddy, P. Ramana
Cognitive radio ad hoc network with intrinsic capabilities of cognitive radio solves the problem in wireless network caused due to limited available spectrum and inefficiency in spectrum usage. Due to spectrum availability, the network topology changes frequently and routing is disrupted. Packet delivery becomes a big problem due to frequent routing disruptions in cognitive radio networks. In this work, a flow controlled multi criteria routing assisted with cooperative caching and packet reconstruction with information redundancy in packet is proposed to improve the QOS in cognitive radio ad hoc network. The multi path routing path selection is guided with four parameters of current buffer occupancy in nodes, predicted link availability time, spectrum availability and cumulative path delay. Different from conventional multi path routing, in this work propagation is controlled in proportion to the prediction based on observed channel quality thereby packet delivery ratio is increased without causing additional network overhead and at lower delay. The performance of the solution is tested against different speed and compared with state of art existing solutions.